The Relationship Between Knowledge And Attitude Of Postpartum Mothers About The Correct Way To Breastfeed Infants With The Incidence Of Breast Milk Gain In The Work Area Of Jeunieb Community Health Center, Jeunieb District, Bireuen Regency - Warzukni, Seri (Universitas Prima Indonesia, 2025)
Breast engorgement is an inflammation of the breast that may or may not be accompanied by infection. Breast engorgement is a breast infection that occurs in 1-2% of breastfeeding women. To determine the relationship between knowledge and attitudes of postpartum mothers about the correct way to breastfeed with the incidence of breast engorgement in the Jeunieb Alue Health Center Work Area, Jeunieb District, Bireuen Regency in 2022. Analytical research design with a cross-sectional approach. The population in this study were all postpartum mothers in the Jeunieb Health Center Work Area, Jeunieb District, Bireuen Regency in 2022, totaling 223 people. Data collection using a questionnaire. The sampling technique used in this study was purposive sampling. To determine the sample size, this study used the Slovin formula so that 69 samples were obtained. The results of the study were that there was a relationship between postpartum mothers' knowledge and the incidence of breast engorgement where the p-value = 0.007 (p-value ≤ 0.05). There is a relationship between attitude and breast milk stagnation where the p-value = 0.000 (p-value ≤ 0.05). It is expected that health workers will increase health promotion to the community, especially counseling on how to breastfeed properly to avoid breast milk stagnation problems. Keywords: Knowledge, Attitude, Breastfeeding ASI